Automatic Analysis Algorithm of Position and Orientation Characteristic Set of Parallel Mechanism based on Neural Network - Wang Gang; Mao Zhiwei; Luo Yufeng; Shi Zhixin (Jixie chuandong)
Based on the theory of the position and orientation characteristic set（ POC）,the theoretical connotation of topology analysis of the parallel mechanism is revealed,a description method of parallel mechanism topology based on neural network is built,an automatic analysis algorithm of parallel mechanism topology mechanism based on neural network is presented. A detailed description of the algorithm in 6 rules parallel mechanism POC set model and the neural network model is introduced,the main steps and examples analysis of the method are given. First of all,by analyzing the topological structure of parallel mechanism,the essence is summed up. Secondly,based on the neural network theory,the topological structure of parallel mechanism is described and digitized. In addition,by analyzing the essential meaning of the automatic analysis of POC sets of parallel mechanisms,the POC neural network model of parallel mechanisms is established and 6 algorithm rules of the model are proposed. Finally,an example is given to prove the correctness and effectiveness of the POC set automatic analysis algorithm for parallel mechanism.